2019
DOI: 10.1186/s13065-019-0556-0
|View full text |Cite
|
Sign up to set email alerts
|

In-silico design, synthesis, ADMET studies and biological evaluation of novel derivatives of Chlorogenic acid against Urease protein and H. Pylori bacterium

Abstract: Background Plants have always played important role in treating human and animal diseases as a therapeutic agent for traditional medicine. Through extensive research throughout the world, potential of natural products have been identified to control the over activity of many enzymes. In - silico screening a library of chlorogenic acid derivatives highlighted some novel compounds which were found effective against urease enzyme and cancer causin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 68 publications
0
13
0
1
Order By: Relevance
“…In silico analyses have predicted several pharmacological activities of CGA, including 1,1-diphenyl-2-picrylhydrazyl radical (DPPH)-free radical scavenging activity. 9,10 This well established antioxidant can slow the postprandial release of glucose into the bloodstream and has been shown to inhibit oxidative stress in human intestinal epithelial cells and reduce/modulate inflammation and neuropathic pain in animal models. [11][12][13] Previous studies have identified CGA as an effective antioxidant, antibiotic, anti-inflammatory and antipyretic agent.…”
Section: Introductionmentioning
confidence: 99%
“…In silico analyses have predicted several pharmacological activities of CGA, including 1,1-diphenyl-2-picrylhydrazyl radical (DPPH)-free radical scavenging activity. 9,10 This well established antioxidant can slow the postprandial release of glucose into the bloodstream and has been shown to inhibit oxidative stress in human intestinal epithelial cells and reduce/modulate inflammation and neuropathic pain in animal models. [11][12][13] Previous studies have identified CGA as an effective antioxidant, antibiotic, anti-inflammatory and antipyretic agent.…”
Section: Introductionmentioning
confidence: 99%
“…Angiotensin II, an important oxidant, alters the binding of LDL-C to its receptors and increases endothelial uptake of LDL-C. Therapy with ACE inhibitors appears to eliminate this untoward effect (Oboh et al, 2014).Hydrogen bond formations, which formed between ligan-protein, most important for proper binding of ligand within the enzyme (Kataria & Khatkar, 2019). Phenolic compounds have the potential to inhibit the activity of ACE with varying doses.…”
Section: Discussionmentioning
confidence: 99%
“…The active site that binds to the two ligands at different amino acid residues shows the other potential of the 8-gingerol content of the ACE gene. This bond's presence causes an increase in bond strength and maintains the interaction between ligands and proteins (Kataria & Khatkar, 2019;S et al, 2020). Van der Waals forces formed on eleven amino acids (THR302, ALA170, PRO163, LYS511, TRP279, GLN369, ASP377, GLU376, ASN374, ASN285, and THR171) provide additional strength, which affects the energy of the bonds formed.…”
Section: Discussionmentioning
confidence: 99%